Faculty experience and engagement in a longitudinal integrated clerkship. (4th May 2017) - Snow, Sarah C.; Gong, Jennifer; Adams, Jennifer E.
Abstract: The authors sought to understand rewards and challenges of teaching third-year medical students in the University of Colorado School of Medicine (CUSOM) Denver Health Longitudinal Integrated Clerkship (DH-LIC) compared to teaching in rotation-based clerkships (RBCs). The authors considered implications for the recruitment and retention of faculty in clinical educational programs. Preceptors completed surveys at baseline and year-end. Of eligible faculty, 28 of 40 completed both baseline and year-end surveys. The majority (85.2%) of faculty were satisfied with the DH-LIC and 85.7% continued to teach in year-two of the program. Faculty reported increased satisfaction from teaching and improved teaching and mentoring skills. Faculty familiarity with DH-LIC students was significantly higher than with students previously taught ( p  = .004); 89.3% of faculty knew their DH-LIC student well enough to tailor instruction to individual learning needs. Teaching techniques utilized at baseline and end of year differed significantly; faculty reported asking questions to promote thinking, providing feedback to students, and providing students with practice in clinical reasoning more frequently in the DH-LIC. Innovative models of education such as LICs offer a strategy to recruit and retain excellent, invested faculty in outpatient settings.